PPAR Gamma Expression Levels during Development of Heart Failure in Patients with Coronary Artery Disease after Coronary Artery Bypass-Grafting - Izabela Wojtkowska; Andrzej Tysarowski; Katarzyna Seliga; Janusz A. Siedlecki; Zbigniew Juraszyński; Milosz Marona; Lidia Greszata; Anna Skrobisz; Karol Kaminski; Robert Sawicki; Janina Stępińska (PPAR Research)
Genetic research has elucidated molecular mechanisms of heart failure (HF). Peroxisome proliferator-activated receptors (PPARs) seem to be important in etiology of HF. The aim of study was to find the correlation between PPARγ expression during development of HF in patients and coronary artery disease (CAD) after coronary artery bypass-grafting (CABG). Methods and Results. We followed up 157 patients (mean age 63) with CAD without clinical, laboratory, or echo parameters of HF who underwent CABG. Clinical and laboratory status were assessed before CABG and at 1, 12, and 24 months. During CABG slices of aorta (Ao) and LV were collected for genetic research. HF was defined as LVEF <40% or NT-proBNP >400 pg/mL or 6MWT <400 m. Patients were divided into 2 groups: with and without HF. PPARγ expression in Ao and LV was not increased in both groups at 2-year follow-up. Sensitivity of PPARγ expression in Ao above 1.1075 in detection of HF was 20.5% (AUC 0.531, 95% CI 0.442–0.619). Positive predictive value (Ppv) was 85.7%. Sensitivity and specificity of PPARγ expression in the LV in detection of HF were 58% and 92.9%, respectively (AUC 0.540, 95% CI 0.452–0.626). Ppv was 73.2%. Conclusion. PPARγ expression in Ao and LV was comparable and should not be used as predictive factor for development of HF in patients with CAD after CABG.